Post-mémoire de Légitime Défense - Kalinowska, Ewa (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The review Légitime Défense, created by a group of Martinican students in Paris,is often presented as a manifesto, more political than literary, without substantial consequences.However, it has induced responses and is remembered in Negro-African intellectualcircles all around the world. With the 90th anniversary of its publication approaching,it seems justifiable to read and analyze the « Avertissement » in order to evaluate its thematicand aesthetic importance.